EFEKTIVITAS BUAH PEPAYA TERHADAP PENURUNAN INDEKS PLAK PADA SISWA/I KELAS VII-2 DI SMP N 1 BATANG KUIS KABUPATEN DELI SERDANG TAHUN 2017 - Netty Jojor Aritonang (Poltekkes Kemenkes Medan, 2019)
Fibrous fruit which contains a lot of water can be consumed as tooth cleaner which can remove plaque fromtooth surface. The result of the laboratory research revealed that 20% of plaque consists of organic and nonorganicsolid substance and 80% of the plaque weight consists of water and 70% of the solid substanceconsists of microorganism. The research was a descriptive survey. It was conducted on Grade VII-2 studentsof SMP N 1 Batang Kuis, Deli Serdang Regency. The population was 216 students, and 35 of them wereused as the samples. The result of the research showed that after chewing papaya, 15 respondents had goodcriteria in their plaque index, 20 respondents had moderate criteria, and no respondent had bad criteria.Theconclusion was that the mean difference in plaque index before and after chewing papaya influenced thedecrease in plaque index which could be seen from the mean difference in plaque index before and afterchewing papaya.